Penetapan Nilai SPF (Sun Protection Factor) Ekstrak Herba Timi (Thymus vulgaris L.) dengan Metode Spektofotometri UV-Vis - Sakti Purwanto, Diyan; Dina Ashfa Karima; Ansela Permata Sari; Malihatul Tsaqif Farras; Wiyanti Sefiana; Mariyam Mariyam; Kalfi Maulana (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Ultraviolet (UV) radiation has been known to cause various adverse effects on the skin, including erythema (commonly referred to as sunburn), premature aging, and, with prolonged exposure, the risk of developing skin cancer. To counteract these harmful effects, sunscreen products are commonly used to protect the skin from UV radiation. The development of natural-based sunscreens is gaining attention due to their potential safety and antioxidant benefits. One promising natural ingredient is thyme (Thymus vulgaris L.), a medicinal herb that contains several secondary metabolites such as flavonoids, alkaloids, and tannins. These compounds possess antioxidant and free radical scavenging properties, making them suitable candidates as active ingredients in sunscreen formulations. This study aims to determine the Sun Protection Factor (SPF) value of thyme herb extract using the UV-Vis spectrophotometric method. A qualitative approach was used to assess the photoprotective potential of the extract. The SPF values were measured at three different concentrations of the extract: 0.5%, 0.75%, and 1.0%. The absorbance of each concentration was recorded at wavelengths ranging from 290 nm to 400 nm using a UV-Vis spectrophotometer. The SPF values were then calculated based on the absorbance data processed using Microsoft Excel. The results revealed that the thyme herb extract exhibited high SPF values at all tested concentrations. Specifically, the SPF values obtained were 36.027 for 0.5%, 36.244 for 0.75%, and 36.516 for 1.0% concentration. All three concentrations fall under the "ultra protection" category, indicating strong UV protective potential. These findings suggest that thyme herb extract can be effectively utilized as a natural active ingredient in the formulation of sunscreen products. Further studies are recommended to explore its stability, safety, and efficacy in topical applications.